Are the developing countries in reality “Exporters of capital”? - Peter Richter (Intereconomics, 1979)
The developing countries have missed no opportunity at any of the great international conferences in recent years to raise the demand for larger capital transfers by the developed countries. Whether compliance with this demand can really contribute to narrowing the North-South gap must however be doubted. According to the following calculations interest payments, royalties and—overt or hidden— profit retransfers have already reached such an amazing dimension that the developing countries would in reality have to be regarded as “capital exporters”.
Keywords: 330; Capital Transfer